Odpowiedź :
Wzór funkcji kwadratowej w postaci ogólnej
[tex]y=ax^2+bx+c[/tex]
a)
[tex]y=(x+4)(x+8)\\\\y=x\cdot x+x\cdot8+4\cdot x+4\cdot8\\\\y=x^2+8x+4x+32\\\\\boxed{y=x^2+12x+32}[/tex]
b)
[tex]y=2(x+3)(x-1)\\\\y=2(x\cdot x-x\cdot1+3\cdot x-3\cdot1)\\\\y=2(x^2-x+3x-3)\\\\y=2(x^2+2x-3)\\\\y=2\cdot x^2+2\cdot2x-2\cdot3\\\\\boxed{y=2x^2+4x-6}[/tex]
Odpowiedź:
1:
(x+4)(x+8)=0
4+x=0
8+x=0
x= -4
x= -8
1x= -8, 2x= -4
2
0=2(x+3)×(x-1)
(x+3)×(x-1)=0
x+3= -3
x+1= -1
1x= -3 2x=-1
Szczegółowe wyjaśnienie:
liczę na naj :3